Analisis Implementasi Good Corporate Governance dalam Proses Pembayaran dan Penagihan Piutang Usaha di PT. BLY - Suryana, Kadek Desinta Maharani; Yuhertiana, Indrawati (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study focuses on the implementation of Good Corporate Governance values such as transparency, accountability, responsibility, independence, and fairness in managing payments and accounts receivable collection at PT. BLY, a galvanizing services company based in Surabaya. Using a qualitative case study approach, data were collected through in-depth interviews and observations over five months. The results indicate that these five principles have been consistently applied, supported by a well-organized recording system, complete documentation, and coordination across divisions. However, challenges such as document delays and potential human errors need to be addressed. Aging reports of receivables and payables reflect healthy financial management. This study recommends improving the information system and staff training to strengthen the implementation of Good Corporate Governance and support the sustainable continuity of PT. BLY’s business.